Escaping Information Poverty through Internet Newsgroups - Hasler, Laura; Ruthven, Ian (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
This paper presents an ongoing investigation into how people use the Internet in an attempt to escape situations of information poverty. We consider posts from a variety of newsgroups which indicate that individuals feel they have nowhere else to go to find information or support for concerns crucial to their everyday lives. A qualitative content analysis is performed to examine three main issues: what information needs people posting to these groups have, who they hide these needs from in the ‘real world’, and why they feel they can only express their needs online. Preliminary findings show that information on health and relationships is most commonly sought. Needs are most often hidden from parents and family, and the main reasons for seeking information online are a lack of understanding and the fact that people simply don’t know where else to go. Our work confirms that newsgroups provide a means of expression for those who feel they have no local support available to them.